Determination of dissipated Energy in Fatigue Crack Propagation Experiments with Lock-In Thermography - Jürgen Bär; Ralf Urbanek (Fracture and Structural Integrity, 2019)
Lock-In thermography can be used to investigate elastic stresses and dissipative effects in dynamic processes like crack propagation. The evaluation normally is performed with a Discrete Fourier Transformation resulting in E- and D-Amplitude and phase images. The E-Amplitude images give information about the stress distribution, the D-Amplitude is connected with dissipated energies. The observed changes in the E-amplitude values can be contributed to a change in the stress state at the crack tip due to bending of the specimen caused by the propagating crack. In the crack propagation experiments the maximum value of the D-Mode in the area in front of the crack tip was found to be constant. The appearance of higher harmonic modes in the evaluation raises the question if the Discrete Fourier Transformation is the appropriate method for a quantitative evaluation of dissipative effects. Experiments performed on flat specimens show that a description of the temperature change due to dissipative effects could not be described with a sine wave with the double loading frequency. Therefore, a quantitative determination of dissipated energies using the Discrete Fourier Transformation is impossible. For a quantitative determination of dissipated energies a new evaluation method has to be developed.